2020
DOI: 10.1111/jnp.12221
|View full text |Cite
|
Sign up to set email alerts
|

Emotional face recognition in autism and in cerebral visual impairments: In search for specificity

Abstract: Autism spectrum disorder (ASD) is characterized by difficulties in the social domain, but also by hyper-and hypo-reactivity. Atypical visual behaviours and processing have often been observed. Nevertheless, several similar signs are also identified in other clinical conditions including cerebral visual impairments (CVI). In the present study, we investigated emotional face categorization in groups of children with ASD and CVI by comparing each group to typically developing individuals (TD) in two tasks. Stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
1
3
1
1
Order By: Relevance
“…We found a main effect of Group, with ASD participants being slower than TD participants. This effect is in line with our expectations and with other studies on face processing in autism (e.g., Grossman et al, 2000;Harms et al, 2010;Kovarski et al, 2019). The exploratory analysis shows that while there is no group difference on the drift rate, meaning that evidence accumulation is similar in both groups, a difference between groups exists on the non-decision time, which is longer in autistic participants.…”
Section: Different Visual Processing Style In Autismsupporting
confidence: 92%
See 3 more Smart Citations
“…We found a main effect of Group, with ASD participants being slower than TD participants. This effect is in line with our expectations and with other studies on face processing in autism (e.g., Grossman et al, 2000;Harms et al, 2010;Kovarski et al, 2019). The exploratory analysis shows that while there is no group difference on the drift rate, meaning that evidence accumulation is similar in both groups, a difference between groups exists on the non-decision time, which is longer in autistic participants.…”
Section: Different Visual Processing Style In Autismsupporting
confidence: 92%
“…Our results are at odds with the Coarse-to-Fine model of visual perception (Bar et al, 2006) and with its extension to faces (Goffaux et al, 2011). Nevertheless, other studies found an HSF advantage during emotional faces categorization (Deruelle & Fagot, 2005;Jahshan et al, 2017;Kovarski et al, 2019;Shankland et al, 2021) and several hypotheses can explain this result in our task, as discussed below.…”
Section: No Evidence Of Top-down Predictions From Lsfcontrasting
confidence: 91%
See 2 more Smart Citations
“…U zadacima u kojima je cilj da se izdvoji jedan određeni stimulus, pored mnogobrojnih distraktora, osobe sa PSA su uspešnije od osoba tipične populacije (TP) (Robertson & Baron-Cohen, 2017). Ovakvi nalazi impliciraju mogućnost drugačijeg načina obrade vizuelnih informacija kod osoba sa PSA (Kovarski et al, 2020).…”
Section: Uvodunclassified